COMPARE: prospective, randomized, non-inferiority trial of high- vs. low-dose paclitaxel drug-coated balloons for femoropopliteal interventions. (28th January 2020) - Steiner, Sabine; Schmidt, Andrej; Zeller, Thomas; Tepe, Gunnar; Thieme, Marcus; Maiwald, Lars; Schröder, Henrik; Euringer, Wulf; Ulrich, Matthias; Brechtel, Klaus; Brucks, Steffen; Blessing, Erwin; et al.
Abstract: Aims: Drug-coated balloons (DCBs) for femoropopliteal interventions have not been tested against each other. We aimed to directly compare efficacy and safety of a high-dose (In.Pact™) vs. low-dose (Ranger™) DCB with nominal paclitaxel densities of 3.5 vs. 2.0 μg/mm 2 . Methods and results: Within a prospective, multicentre, non-inferiority, clinical trial 414 patients with symptomatic femoropopliteal lesions (Rutherford classification 2–4) were randomly assigned in a 1:1 ratio to endovascular treatment with either high- or low-dose DCB after stratification for lesion length. Primary efficacy and safety endpoints comprised primary patency and freedom from major adverse events (i.e. device and procedure-related deaths through 1 month, major amputations, and clinically driven target lesion revascularization through 12 months). We set a non-inferiority margin of −10% at 12 months. Total occlusions were observed frequently (>40%) and provisional stenting was performed in every fourth intervention. Non-inferiority was determined for both primary efficacy and safety endpoints at 12 months. Primary patency was 81.5% in the high-dose and 83.0% in low-dose DCB group difference: 1.5% [lower bound of the 90% two-sided confidence interval (CI) −5.2%]; P non-inferiority < 0.01. Freedom from major adverse events was determined in 92.6% in high-dose and in 91.0% in low-dose DCB group [difference −1.6% (lower bound of the 90% two-sided CI −6.5%); P non-inferiority < 0.01]. Overall death rate was low (2.0%) and no major amputation occurred. Conclusion: Two DCBs with different coating characteristics exhibited comparable results with excellent effectiveness and safety through 12 months for femoropopliteal interventions including a wide range of lesion lengths. Clinical trial registration: The trial is registered with ClinicalTrials.gov (NCT02701543).